The development of malay boys’ and girls’ schools, school libraries and literacy in the federated malay states and the unfederated malay states during british indirect rule, 1894-1941 - Lim , Peng Han (Persatuan Pustakawan Malaysia, 2011)
The British began to colonize the Malay Peninsular by occupying Penang (1786), Malacca (1795) and Singapore (1819) to form the Straits Settlements in 1826. The state of Perak, Selangor, Pahang and Negri Sembilan later known as the Federated Malay States (FMS) voluntarily put themselves under British protection beginning 1874. The Federal Inspector of Schools was appointed to oversee the expansion of Malay schools. By 1909 Johore, Kedah, Perlis, Kelantan and Trengganu, later known as the Unfederated Malay States came under British suzerainty. In 1931 43 per cent of Malay boys age 5 – 14 and 23 per cent of Malay boys of the same age were enrolled in Malay boys’ schools in the FMS and UMS respectively. Less than 7 per cent of Malay girls in the same age group in the FMS and UMS were enrolled in Malay girls’ schools. There were only known records school libraries in Malay boys’ schools in Negri Sembilan and Selangor, although limited books were made available. There were no records of school libraries in Malay girls schools in the FMS and UMS. The promotion of literacy was restricted by the incidence enrolment in schools, insufficient production of Malay books and insufficient school libraries.